Adventures of Huckleberry Finn - Twain, Mark, 1835-1910.; Elliott, Emory, 1942-2009. (Oxford ; New York : Oxford University Press, 1999)
You don't know about me, without you have read a book by the name of "The Adventures of Tom Sawyer", but that ain't no matter.' So begins, in characteristic fashion, one of the greatest American novels. Narrated by a poor, illiterate white boy living in America's deep South before the Civil War, Adventures of Huckleberry Finn is the story of Huck's escape from his brutal father and the relationship that grows between him and Jim, the slave who is fleeing from an even more brutal oppression. As they journey down the Mississippi their adventures address some of the most profound human.
Includes bibliographical references (pages xliii-l).
Print version record.
eBooks on EBSCOhost
Keywords: Finn, Huckleberry -- (Fictitious character) -- Fiction; Finn, Huckleberry -- (Fictitious character); Mississippi River -- Fiction; Runaway children -- Fiction; Male friendship -- Fiction; Fugitive slaves -- Fiction; Race relations -- Fiction; Missouri -- Fiction; Boys -- Fiction; Coming of age -- Fiction; Mississippi (Fleuve) -- Romans, nouvelles, etc; Enfants fugueurs -- Romans, nouvelles, etc; Amitié masculine -- Romans, nouvelles, etc; Esclaves fugitifs -- Romans, nouvelles, etc; Relations raciales -- Romans, nouvelles, etc; Missouri -- Romans, nouvelles, etc; Garçons -- Romans, nouvelles, etc; Boys; Fugitive slaves; Male friendship; Race relations; Runaway children; Mississippi River; Missouri; Finn, Huckleberry (Fictional character) -- Fiction; Mississippi River -- Fiction; Runaway children -- Fiction; Friendship -- Fiction; Fugitive slaves -- Fiction; Race relations -- Fiction; Missouri -- Fiction; Boys -- Fiction; Humorous fiction; Bildungsromans; Action and adventure fiction; Fiction; Adventure fiction; Humorous fiction; Bildungsromans; Action and adventure fiction; Humorous fiction; Bildungsromans